2011
DOI: 10.3390/ijms12074294
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Gentamicin Using Poly(3-hydroxybutyrate) Microspheres

Abstract: Poly(3-hydroxybutyrate), P(3HB), produced from Bacillus cereus SPV using a simple glucose feeding strategy was used to fabricate P(3HB) microspheres using a solid-in-oil-water (s/o/w) technique. For this study, several parameters such as polymer concentration, surfactant and stirring rates were varied in order to determine their effect on microsphere characteristics. The average size of the microspheres was in the range of 2 μm to 1.54 μm with specific surface areas varying between 9.60 m2/g and 6.05 m2/g. Low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 24 publications
7
65
0
Order By: Relevance
“…In one study, gentamycin (GEN) was not only encapsulated into the microspheres, but also superficially absorbed on the external surface of microspheres. The mentioned study showed the initial release, including 60% of the entire encapsulated drug (16). In this study, slow and controlled release of drug occurred following the initial burst.…”
Section: Drug Release Ratementioning
confidence: 88%
See 3 more Smart Citations
“…In one study, gentamycin (GEN) was not only encapsulated into the microspheres, but also superficially absorbed on the external surface of microspheres. The mentioned study showed the initial release, including 60% of the entire encapsulated drug (16). In this study, slow and controlled release of drug occurred following the initial burst.…”
Section: Drug Release Ratementioning
confidence: 88%
“…Slower release of the drug by larger microspheres is due to the decreased path of drug diffusion inside the microspheres and decreased specific superficial areas in larger microspheres compared to smaller ones. In one previous study, drug release during 24 hours was related to the small size of microspheres (1.54 μm) (16). Drug release under in vitro condition also depends on drug diffusion within the microspheres.…”
Section: Influential Factors On Drug Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Impediment of the emulsification efficiency at a given stirring rate may occur due to insufficient amount of surfactant as in case of low lecithin concentration or due to viscosity increase by higher span 80 concentration delivering larger MS (Francis et al, 2011). The larger particles, obtained with both surfactants, have a smaller surface area to volume ratio and thus a lower potential for drug escape to the external phase (Li et al, 1999).…”
Section: Discussionmentioning
confidence: 99%